Perbandingan Gejala PMS Antara Siswi Yang Aktif Dan Tidak Aktif Olahraga Lari Pada Siswi Di Smp Penanggungan Ngoro-Trawas Mojokerto - Eka Nonitasari; Ika Khusnia (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2019)
Premenstrual Syndrome is a combination of symptoms of physical distress, psychological, and behavioral change in which the symptoms are so severe that it interferes daily activities. Many women who experience disturbance before or during menstruation. This study was conducted to compare premenstrual syndrome among female students who have active and inactive sport in SMP PENANGGUNGAN Ngoro-Trawas. This study used a descriptive design. Population taken all the girls at SMP PENANGGUNGAN Ngoro-Trawas with a sample of 133 people that’s selected by consecutive samplin. of data collection using questionnaires and interviews. The variables in this study consisted of two variables, the are variable track the symptoms of PMS. The results of this study obtained a minority of respondents are actively running experiencing <50% symptoms of PMS as many as six respondents (4.5%), and most respondents did not actively exercise ≥ 50% experienced symptoms of PMS as many as 125 respondents ( 94%). This is obtained because the student is not active sport girl sport considered when experiencing PMS can only aggravate the pain but with exercise can decrease PMS symptoms.When jogging is done regularly for three times a week with a frequency of 20-45 minutes, will reduce the symptoms of PMS like symptoms characterized by physical, headache, pain pungggung, aching rheumatic pain, acne, breast tenderness, heavy legs, abdominal pain bottom, flatulence, diarrhea, often hungry, and mental symptoms are marked with an uneasy feeling, irritability, insomnia, anxiety, depression, and personality seemed to disappear. Therefore, students should be more motivated by the problem of PMS symptoms and can be run with regular exercise for 3 times a week, and applied in everyday life.